Effect of Weld Groove Type Variations on Deformation in Structural Carbon Steel Butt Joint Welding Using the Finite Element Method - Muhammad Daffa Dzaky; Delima Yanti Sari; Waskito Waskito; Junil Adri (Jurnal Vokasi Mekanika (VoMek), 2025)
Deformation in welded joints can reduce the precision, strength, and service life of a structure, especially in structural carbon steel commonly used in the construction industry. One of the main factors influencing deformation is the type and angle of the weld groove. This study aims to analyze the effect of groove type and angle variations on deformation in butt joint welding of structural carbon steel. The method used is a numerical simulation based on the Finite Element Method (FEM) using ANSYS software, consisting of transient thermal and transient structural analyses. The groove variations include V-grooves with angles of 45°, 60°, and 75°, as well as U-grooves with angles of 50°, 60°, and 70°. The simulation results show that the V-groove with a 45° angle produces the maximum deformation of 2.1317 mm, while the U-groove with a 70° angle results in the minimum deformation of 0.23808 mm. These findings indicate that U-grooves generally produce lower deformation compared to V-grooves. Therefore, selecting the appropriate groove design can enhance the quality of weld joints and the overall structural performance.